2019
DOI: 10.1007/jhep04(2019)009
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement and chaos in warped conformal field theories

Abstract: Various aspects of warped conformal field theories (WCFTs) are studied including entanglement entropy on excited states, the Rényi entropy after a local quench, and out-of-time-order four-point functions. Assuming a large central charge and dominance of the vacuum block in the conformal block expansion, (i) we calculate the single-interval entanglement entropy on an excited state, matching previous finite temperature results by changing the ensemble; and (ii) we show that WCFTs are maximally chaotic, a result … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 71 publications
(184 reference statements)
2
35
0
Order By: Relevance
“…Moreover, the Rényi entanglement entropy has been used as a very helpful quantity to measure the properties of the vacuum state and excited states [55][56][57][58][59][60][61][62][63][64][65][66]. In the undeformed CFTs, the nth Rényi entanglement entropy S (n) A has been extensively studied in the literature [58][59][60][61][64][65][66][67][68][69][70][71][72][73][74]. In rational CFTs, it has been shown that the excess of the Rényi entanglement entropy has to be the logarithmic of quantum dimension [59] of the corresponding local operator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Rényi entanglement entropy has been used as a very helpful quantity to measure the properties of the vacuum state and excited states [55][56][57][58][59][60][61][62][63][64][65][66]. In the undeformed CFTs, the nth Rényi entanglement entropy S (n) A has been extensively studied in the literature [58][59][60][61][64][65][66][67][68][69][70][71][72][73][74]. In rational CFTs, it has been shown that the excess of the Rényi entanglement entropy has to be the logarithmic of quantum dimension [59] of the corresponding local operator.…”
Section: Introductionmentioning
confidence: 99%
“…As applications, we employ the formula to investigate the Rényi entanglement entropy in two-dimensional CFTs perturbatively. We just put a local primary operator following the procedure in [59][60][61][64][65][66] to obtain a locally excited state. With time evolution, the excess of Rényi entanglement entropy of deformed two-dimensional CFTs has been calculated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Many of their unique field theoretic properties have been uncovered in recent years [16][17][18][19][20][21][22][23][24][25][26][27]. In a holographic context, their natural counterparts are gravitational theories that admit Warped AdS 3 (WAdS 3 ) spacetimes as solutions [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…In CFT, this quantity can be calculated in terms of a correlator [7,8] and has already studied in RCFTs [9,10], holographic CFTs [11,12], and also non-perturbatively in pure CFTs [1,13,14]. (See also [11,[15][16][17][18][19][20], which revealed the growth of the entanglement entropy after a local quench in other setups.) It is interesting to note that the entanglement growth in RCFTs approaches constant in the late time limit, on the other hand, the entanglement entropy in holographic CFTs shows a logarithmic growth.…”
Section: Introductionmentioning
confidence: 99%